Fraud Diamond Analysis In Fraudulent Financial Statement Detection Using Beneish M-Score - Meri Kristianti; Carmel Meiden (Jurnal Riset Akuntansi Terpadu, 2021)
Companies, especially go public companies, tend to want to display financial statements that look healthy and profitable to attract the attention of investors and potential investors. Therefore, sometimes companies commit fraud in financial statements to fulfill these objectives. This study was conducted to empirically test whether the fraud diamond element has an effect on the possibility of fraudulent financial statements in manufacturing sector companies listed on the Indonesia Stock Exchange in 2017-2019 with the Beneish M-Score as a proxy for the dependent variable. There are 120 total samples obtained by purposive sampling method with analytical techniques using descriptive statistical tests and logistic regression tests. The results of this study indicate that the nature of industry and rationalization variables have a positive and significant effect on the possibility of fraudulent financial statements, but for the variables of financial stability, external pressure, personal financial need, financial target, ineffective monitoring and capability, it is not proven to have a significant effect on the possibility of fraudulent financial statements.